2014
DOI: 10.4028/www.scientific.net/amr.955-959.2526
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Processes of Anoxic/Oxic Bioreactor and Artificial Wetland for Rural Domestic Wastewater Treatment

Abstract: This paper examined the treatment of rural domestic wastewater. Influent and effluent samples were experimented for Chemical oxygen demand (COD), NH4+-N, NO3--N and TP in the Taihu Lake Environmental laboratory of Southeast University in Wuxi. Different hydraulic retention time (HRT) and recycle ratios were applied to appraise their influence on removal efficiency. The wastewater temperature was controlled between 20 to 24°C and pH ranges 7.6 – 8.1. The result revealed average COD, NH4+-N, NO3--N and TP remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…3. This agreed with the findings of Ladu et al [32], who studied the effects of three different HRTs on the efficiency of anaerobic filters while treating domestic wastewater, and found that the efficiency of the reactor increased by increasing HRT (from one to three days). Furthermore, they observed a 32% reduction in COD values at HRT of one day, 40% at HRT of two days and 44% at HRT of three days.…”
Section: Carbonaceous and Nitrogenous Pollutant Removal By Pilot-scalsupporting
confidence: 92%
See 2 more Smart Citations
“…3. This agreed with the findings of Ladu et al [32], who studied the effects of three different HRTs on the efficiency of anaerobic filters while treating domestic wastewater, and found that the efficiency of the reactor increased by increasing HRT (from one to three days). Furthermore, they observed a 32% reduction in COD values at HRT of one day, 40% at HRT of two days and 44% at HRT of three days.…”
Section: Carbonaceous and Nitrogenous Pollutant Removal By Pilot-scalsupporting
confidence: 92%
“…5. Different researchers have reported that the efficiency of a reactor for removing TN from wastewater largely depends on the ratio of COD to TN concentrations (COD/TN) along with reactor configuration [32,42]. Ladu et al [32] reported more than 75% TN removal efficiency in a sequencing batch reactor at a COD/ TN ratio of greater than 3.9, while Wang et al [42] reported a 37-41% reduction in TN concentration at a COD/TN ratio of 7.2.…”
Section: Carbonaceous and Nitrogenous Pollutant Removal By Pilot-scalmentioning
confidence: 99%
See 1 more Smart Citation